2015
DOI: 10.1590/1809-4430-eng.agric.v35n1p76-88/2015
|View full text |Cite
|
Sign up to set email alerts
|

Weather variables, water balance, growth, and agro industrial yield of sugarcane

Abstract: ABSTRACT:The objective of this study was to evaluate the meteorological variables, water deficiency, growth, and agro-industrial yield of sugarcane varieties: RB72454, RB863129, RB867515, RB92579, RB93509, RB931003, RB951541, and RB971755, in rainfed crop in two harvests in the Rio Largo-AL region. The meteorological variables were obtained in an automatic station and water balance was done by Thornthwaite & Mather method. During the study period, the air temperature ranged from 16.6 to 35.9 ºC. In the first p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…The agro-industrial productivity of sugarcane is extremely dependent of the rainfall distribution over the production cycles. This effect was observed by Teodoro et al (2015) and Abreu et al (2013), who found that, in the cycle in which there was a higher water deficit, agricultural and agro-industrial productivity were affected significantly. This, for that the yields from the sugarcane industry are not impaired, depending on the amount and uniformity of rainfall distribution, the use of irrigation is required (TEODORO et al, 2009).…”
Section: Introductionmentioning
confidence: 61%
“…The agro-industrial productivity of sugarcane is extremely dependent of the rainfall distribution over the production cycles. This effect was observed by Teodoro et al (2015) and Abreu et al (2013), who found that, in the cycle in which there was a higher water deficit, agricultural and agro-industrial productivity were affected significantly. This, for that the yields from the sugarcane industry are not impaired, depending on the amount and uniformity of rainfall distribution, the use of irrigation is required (TEODORO et al, 2009).…”
Section: Introductionmentioning
confidence: 61%
“…Silva et al (2015), no município de Capim-PB, testando diferentes métodos de estimativa da evapotranspiração, encontraram valores médios ao longo de um ciclo da cultura de 3,74 a 4,86 mm dia -1 . Além de Teodoro et al (2015), que encontraram valores de evapotranspiração de 1,58 a 5,9 mm dia -1 e observaram valores com maior amplitude.…”
Section: Resultsunclassified
“…Abreu et al (2013) analyzed the productivity of six varieties for three cycles, and this variety stood out in plant crop cultivation. In many variety competition experiments conducted in Northeastern Brazil, this variety has stood out (Abreu et al, 2013;Almeida et al, 2008;Teodoro et al, 2015). For ratoon crop cultivation, the model overestimated by 11%.…”
Section: Evaluation Of the Dssat/canegro Model Growth Variables Analysesmentioning
confidence: 99%